SCIENCE FAIRS AND INTEGRATED PROJECT EXHIBITIONS AS AN INNOVATIVE SPACE FOR RESEARCH, TEACHING, AND OUTREACH: AN EXPERIENCE REPORT WITH VOCATIONAL TRAINING COURSES - Teles, Mairla Meneses Lopes (Seven Editora, 2026)
Vocational and Technological Education (VTE), at both technical and higher education levels, faces the challenge of overcoming excessively instrumentalized training models, strongly oriented towards the logic of efficiency and immediate adaptation to the labor market. In this context, science fairs and integrated project exhibitions emerge as pedagogical and institutional strategies capable of articulating teaching, research, and outreach in a critical, contextualized, and socially committed way. This article aims to analyze the experiences of outreach projects, discussing their contributions to technical-professional training and their social impacts. Methodologically, this is a qualitative, descriptive research, based on experience reports, with data production through document analysis, participant observation, and evaluations by participants and the organizing team, analyzed according to thematic content analysis. The results show that extension programs promote broad academic and social mobilization, with significant participation from students, faculty, and the external community, in addition to strengthening student leadership, interdisciplinarity, the articulation between theory and practice, and the development of skills such as communication, teamwork, critical thinking, and social responsibility. It is concluded that science fairs and integrated exhibitions constitute innovative spaces for training in vocational and technological education, contributing to meaningful learning and strengthening the social role of extension programs. DOI: https://doi.org/10.56238/sevened2026.008-002